Aqueous dispersion composition comprising ethylene-carboxylic acid copolymer
By incorporating a polymeric wax as an anti-blocking agent in water dispersion compositions containing ethylene-carboxylic acid copolymers, the issue of blocking and reduced adhesion reliability is addressed, achieving improved adhesion and mechanical strength.
Patent Information
- Application Number
- JP2025009171
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-10-11
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-23
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Water dispersion compositions containing ethylene-carboxylic acid copolymers face issues with adhesion reliability due to blocking phenomena during storage, which affect the mechanical properties of the adhesive layer.
Incorporating a polymeric wax with at least 5% by weight based on the weight of the ethylene-carboxylic acid copolymer, having a peak area of 50% or more at a melting point of 80° C. or less, acts as an anti-blocking agent, reducing blocking and maintaining adhesion reliability.
The use of a natural wax-based anti-blocking agent significantly reduces blocking phenomena during storage while maintaining the desired adhesion properties, ensuring reliable adhesion and mechanical strength of the adhesive layer.
Smart Images

Figure 2025066787000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-dispersed composition containing an ethylene-carboxylic acid copolymer, and more specifically, to a water-dispersed composition containing an ethylene-carboxylic acid copolymer and an additive. [Background technology]
[0002] For example, ethylene-carboxylic acid copolymers such as ethylene-acrylic acid copolymers are utilized in various applications such as sealing materials, adhesives, packing materials, optical films, etc. Ethylene-acrylic acid copolymers can be produced in the form of an aqueous dispersion and used for forming coating films or adhesive layers.
[0003] For example, the aqueous dispersions can be used to form adhesive or fusing layers by coating the surfaces of polymeric films, papers, metal foils, fabrics, and the like and applying heat.
[0004] Ethylene-carboxylic acid copolymers contain acid groups in the copolymer structure and have adhesive properties in themselves. Therefore, during storage of the dispersion, a blocking phenomenon may occur in which the dispersion sticks to other media such as containers. If an additive such as an anti-blocking agent is added to the dispersion to eliminate the blocking phenomenon, the adhesive strength of the dispersion and the mechanical properties of the adhesive layer formed therefrom may decrease.
[0005] Taking the above aspects into consideration, it is necessary to design a composition that can maintain adhesive reliability.
[0006] For example, International Patent Publications WO2005 / 085331 and WO2017 / 050589 disclose the formation of heat sealable coatings using aqueous polymer dispersions. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a water-dispersed composition containing an ethylene-carboxylic acid copolymer having improved adhesive reliability. [Means for solving the problem]
[0008] The water-dispersed composition according to an exemplary embodiment may include an ethylene-carboxylic acid copolymer, an antiblocking agent including a polymer wax contained in an amount of 5% by weight or more based on the weight of the ethylene-carboxylic acid copolymer and having a peak area of 50% or more at a melting point of 80° C. or less in a differential scanning calorimetry (DSC) graph, and an aqueous dispersion medium.
[0009] In some embodiments, the polymer wax may have a weight average molecular weight (Mw) of 500 to 1,500.
[0010] In some embodiments, the polymeric wax may have a polydispersity index (PDI) of 1-4.
[0011] In some embodiments, the ethylene-carboxylic acid copolymer can include an ethylene-acrylic acid (EAA) copolymer.
[0012] In some embodiments, the EAA copolymer may have an ethylene content of 75 to 85% by weight and an acrylic acid content of 15 to 25% by weight.
[0013] In some embodiments, the ethylene-carboxylic acid copolymer may have a melt flow index (MFI) measured under conditions of 190° C. and 2.16 kg of 250 to 1,500 g / 10 min.
[0014] In some embodiments, the aqueous dispersion composition further comprises a neutralizing agent, and the ethylene-carboxylic acid copolymer may have a degree of neutralization of 40 to 100%.
[0015] In some embodiments, the neutralizing agent may include ammonia or an alkali metal salt.
[0016] In some embodiments, the content of the antiblocking agent may be 5 to 10% by weight based on the weight of the ethylene-carboxylic acid copolymer.
[0017] In some embodiments, the solids content of the aqueous dispersion composition may be 20-50%. Effect of the Invention
[0018] According to an exemplary embodiment, the water-dispersed composition can include a natural wax-based antiblocking agent having a predetermined melting point range together with the ethylene-carboxylic acid copolymer, which can significantly reduce the blocking phenomenon during storage while maintaining a desired adhesive strength.
[0019] The aqueous dispersion composition may further include a neutralizing agent, and the physical properties and content of the ethylene-carboxylic acid copolymer and the neutralizing agent may also be adjusted to maintain a good balance between adhesive strength and anti-blocking properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The water-dispersed composition according to an embodiment of the present invention includes an ethylene-carboxylic acid copolymer, an antiblocking agent, and an aqueous dispersion medium (eg, water), and may further include a neutralizing agent.
[0021] The ethylene-carboxylic acid copolymer may be produced by a copolymerization reaction of ethylene and a carboxylic acid monomer. According to an exemplary embodiment, the carboxylic acid monomer may be acrylic acid. In this case, the ethylene-carboxylic acid copolymer may include an ethylene-acrylic acid (EAA) copolymer.
[0022] The term "acrylic acid" as used in this application is intended to include methacrylic acid, and may also be intended to include its esterified products (eg, acrylate, methacrylate).
[0023] In the following, an example will be described in which an EAA copolymer is used as the ethylene-carboxylic acid copolymer.
[0024] The EAA copolymers can be tailored in physical properties to provide a substantially coatable viscous fluid to achieve the coating characteristics of the water-dispersed composition.
[0025] In some embodiments, the content of acrylic acid (e.g., acrylic acid-derived units or acrylic acid-derived blocks) in the total weight of the EAA copolymer may be 15 to 25 wt %, in which case the content of ethylene (e.g., ethylene-derived units or ethylene-derived blocks) may be 75 to 85 wt %.
[0026] When the content of acrylic acid is relatively small, the adhesive strength to a hydrophobic substrate (e.g., a resin substrate such as polyolefin) may be improved. When the content of acrylic acid is high, it may be difficult to efficiently produce the copolymer due to problems such as the generation of polyacrylic acid in the manufacturing process. Therefore, by adjusting the content of acrylic acid to the above-mentioned range, the adhesive strength of the coating layer or sealing layer containing the ethylene-acrylic acid copolymer can be improved.
[0027] In some embodiments, the EAA copolymer may have a melt flow index (MFI) of 250 to 1,500 g / 10 min under conditions of 190° C. and 2.16 kg. Within this range, the flowability of the water-dispersed composition can be increased to improve the coating properties, and the heat resistance and mechanical strength of the adhesive or seal layer formed from the water-dispersed composition can be prevented from excessively decreasing.
[0028] In some embodiments, the degree of neutralization of the EAA copolymer may be from 40 to 100%, preferably from 40 to 80%, and more preferably from 45 to 80%.
[0029] The term "neutralization degree" used in this application may refer to the proportion of acid groups (carboxylic acid groups) contained in the EAA copolymer that have been reacted or neutralized by a neutralizing agent. Within the range of neutralization degree, excessive viscosity increase of the aqueous dispersion composition is suppressed, and sufficient dispersibility and coating uniformity can be ensured.
[0030] A neutralizing agent, as described above, can be included to at least partially neutralize the acid groups of the EAA copolymer. The neutralizing agent can, for example, be mixed with the EAA copolymer to provide a substantially water-dispersed composition as a coatable viscous fluid.
[0031] As the neutralizing agent, any basic compound can be used without particular limitation. In a preferred embodiment, the neutralizing agent can include an organic base such as ammonia or an amine-based compound. The neutralizing agent can also include an alkali metal salt such as LiOH, KOH, NaOH, or CsOH. These can be used alone or in combination of two or more.
[0032] If the amount of neutralizing agent is too small, the preparation of the dispersion may be substantially difficult and a blocking phenomenon may be caused by the acid groups of the EAA copolymer.
[0033] If the amount of neutralizing agent is too high, the viscosity of the water-dispersed composition may increase, deteriorating the coating properties, and the adhesive properties may also decrease.
[0034] In one embodiment, when ammonia is used as the neutralizing agent, the content of the neutralizing agent may be 10% by weight or less (e.g., 1 to 10% by weight, 5 to 10% by weight) based on the total weight of the composition. When the above-mentioned alkali metal salt is used as the neutralizing agent, the content of the neutralizing agent may be 1% by weight or less (e.g., 0.1 to 1% by weight, 0.5 to 1% by weight) based on the total weight of the composition.
[0035] According to an exemplary embodiment, the water-dispersed composition may include a wax or paraffin-based antiblocking agent.
[0036] For example, to form a water dispersion, the acid group of the EAA copolymer can be partially neutralized with the neutralizing agent described above. However, in the case of a neutralizing agent such as ammonia (or aqueous ammonia (NH4OH)), it may be easily volatilized or evaporated, and the acid group may be excessively exposed or remain. Therefore, a blocking phenomenon may occur in which the water dispersion composition sticks to a container or other medium during storage.
[0037] In contrast, the aqueous dispersion composition according to the exemplary embodiment further includes an antiblocking agent, thereby reducing or suppressing the blocking phenomenon while maintaining the adhesive strength of the composition.
[0038] In some embodiments, the antiblocking agent can include natural waxes or paraffin-based materials, such as microcrystalline waxes, natural waxes, synthetic waxes, Fischer-Tropsch waxes, polyethylene-based waxes, and the like.
[0039] In a preferred embodiment, the antiblocking agent may be a polymer wax having a melting point (Tm) of 80° C. or less. For example, a polymer wax may be used in which a plurality of Tm peaks are generated in a graph obtained by differential scanning calorimetry (DSC), and the peak area of the Tm peaks at 80° C. or less is 50% or more of the total peak area.
[0040] Polymeric waxes having melting points in the aforementioned ranges can be used to provide substantial anti-blocking properties.
[0041] In some embodiments, the weight average molecular weight (Mw) of the antiblocking agent may be in the range of 500 to 1,500. Within this range, the antiblocking properties can be sufficiently realized without increasing the viscosity of the aqueous dispersion composition.
[0042] In one embodiment, the polydispersity index (PDI) of the antiblocking agent may be 1 to 4. Within this range, the generation of non-dispersible components due to a decrease in uniformity of the molecular weight distribution can be prevented, and an excessive increase in viscosity of the water-dispersed composition can be suppressed.
[0043] In some embodiments, the content of the antiblocking agent may be 5% by weight or more based on the total weight of the EAA copolymer. If the content of the antiblocking agent is less than 5% by weight, the antiblocking properties may not be substantially realized. In a preferred embodiment, the content of the antiblocking agent may be in the range of 5 to 10% by weight based on the total weight of the EAA copolymer.
[0044] The content of the solid content in the water dispersion composition may be 20 to 50% by weight, preferably 25 to 30%. Within this range, the volatile components can be easily removed at low temperatures, and an adhesive layer or a seal layer can be formed.
[0045] The aqueous dispersion composition can be used as a sealing material for packaging films containing polyethylene, polypropylene, polymethyl methacrylate, polyethylene terephthalate, etc. For example, after coating the surface of the sealing portion of a packaging film with the aqueous dispersion composition, a sealing layer or an adhesive layer can be easily formed by thermocompression bonding.
[0046] The aqueous dispersion composition can also be used to form insulating structures such as adhesive layers, antistatic layers, and encapsulation layers by coating various objects such as paper, resin films, and metal foils.
[0047] The aqueous dispersion composition may further contain other additives within the range that does not impair the physical properties such as dispersibility and thermal properties of the EAA copolymer. For example, the additives may include an antistatic agent, a surfactant, inorganic particles, etc.
[0048] In the following, specific examples are presented to aid in understanding the present invention, but these examples are merely illustrative of the present invention and do not limit the scope of the appended claims. It is clear to those skilled in the art that various changes and modifications can be made to these examples within the scope of the scope and technical ideas of the present invention, and it is natural that these changes and modifications fall within the scope of the appended claims.
[0049] Examples and Comparative Examples An aqueous dispersion composition containing an EAA copolymer with a neutralization degree of 80% and a total solid content of 25% was prepared. The aqueous dispersion composition contained a wax-based antiblocking agent of the type and content shown in Table 1 below, and the aqueous dispersion compositions of the examples and comparative examples were prepared.
[0050] In the cases of Comparative Examples 5 and 6, the antiblocking agent was omitted and only the neutralizing agent was added.
[0051] Experimental Example (1) Measurement of the molecular weight of the antiblocking agent 5 mg of each antiblocking agent was dissolved in 1M of 1,2,4-trichlorobenzene containing 200 ppm of butylated hydroxytoluene (BHT), which was used as the eluent of the system. The samples were prepared by stirring at 150°C for 4 hours using a sample preparation device (Agilent PL-SP 260 VS Sample Preparation System).
[0052] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the sample were measured using a GPC system (PL-GPC220, Agilent) equipped with a refractive index detector and polystyrene standards.
[0053] The measured Mw and Mn were used to calculate the PDI (Mw / Mn).
[0054] (2) Measurement of the melting point of the antiblocking agent The melting point was measured by using a Differential Scanning Calorimeter (measuring device: Q20 manufactured by TA Corporation).
[0055] Specifically, a 10 mg sample of the antiblocking agent was taken, placed in an aluminum crucible, and covered with a lid containing a pinhole.
[0056] While supplying nitrogen at a flow rate of 50 mL / min as a purge gas, the temperature was raised from -50 to 180°C at 10°C / min (first heating section), and then the temperature was kept isothermal at 180°C for 1 minute. The sample was then cooled from 180°C to -50°C at a rate of 10°C / min to crystallize. In the second heating section, the temperature was changed from -50 to 180°C at 10°C / min, and the temperature (Tm) of the melting peak occurring in the second heating section was measured, and the proportion of the peak area below 80°C was calculated.
[0057] (3) Blocking force of the water-dispersed composition The evaluation was performed based on the Blocking Resistance Method B test method of ISO 11502 as follows (measuring device: Instron). A test piece of the substrate coated with the water-dispersed composition was prepared with a size of 760 x 100 mm. The substrate coated with the water-dispersed composition and the uncoated substrate were placed in contact with each other, and a load of 2.3 kg was applied, and the substrate was left at 50 degrees for 3 hours, and then left in a constant temperature and humidity room for 24 hours. Aluminum blocks of 100 x 100 mm were hung on the top and bottom of a tensile tester, and the test piece was fixed between the aluminum blocks and pulled at a speed of 500 mm / min, and the maximum force was measured.
[0058] (4) Measurement of heat seal strength of water-dispersed composition The measurements were made according to ASTM F88 as follows (measuring device: Instron). A test piece of 250 x 10 mm size was prepared using a device (Gradient Heat Seal Tester) conforming to ASTM F2029. A substrate coated with the water-dispersed composition and an uncoated substrate were placed in contact with each other and then bonded at a constant temperature for 1 sec at 2 bar. After leaving the specimen in a constant temperature and humidity room for 24 hours, the specimen was engaged at the top and bottom with a tensile tester, pulled at a speed of 300 mm / min, and the average force was measured over a constant section.
[0059] The measurement results are summarized in Table 1 below.
[0060] [Table 1]
[0061] Referring to Table 1, in the case of the antiblocking agent-containing water-dispersed composition of the example, the blocking force was reduced and a stable thermal adhesive force was achieved.
[0062] In the cases of Comparative Examples 1 to 3 in which the Tm peak area of the wax was reduced to less than 50%, and Comparative Examples 5 and 6 in which no wax was added, the blocking force increased or the thermal adhesive force significantly decreased.
[0063] In the case of Comparative Example 4, where the wax content was 3% by weight, substantially no anti-blocking properties were achieved.
Claims
1. an ethylene-carboxylic acid copolymer; an antiblocking agent including a polymer wax contained in an amount of 5% by weight or more based on the weight of the ethylene-carboxylic acid copolymer, the polymer wax having a peak area of 50% or more at a melting point of 80° C. or less in a differential scanning calorimetry (DSC) graph; and an aqueous dispersion medium.
2. The water-dispersed composition according to claim 1, wherein the polymer wax has a weight average molecular weight (Mw) of 500 to 1,500.
3. The water-dispersed composition according to claim 1, wherein the polymer wax has a polydispersity index (PDI) of 1 to 4.
4. The water-dispersed composition of claim 1, wherein the ethylene-carboxylic acid copolymer comprises an ethylene-acrylic acid (EAA) copolymer.
5. 5. The water-dispersed composition according to claim 4, wherein the EAA copolymer contains 75 to 85% by weight of ethylene and 15 to 25% by weight of acrylic acid.
6. The water-dispersed composition according to claim 1, wherein the ethylene-carboxylic acid copolymer has a melt flow index (MFI) of 250 to 1,500 g / 10 min measured under conditions of 190° C. and 2.16 kg.
7. Further comprising a neutralizing agent, 2. The water-dispersed composition according to claim 1, wherein the ethylene-carboxylic acid copolymer has a degree of neutralization of 40 to 100%.
8. The water-dispersed composition of claim 7 , wherein the neutralizing agent comprises ammonia or an alkali metal salt.
9. 2. The water-dispersed composition according to claim 1, wherein the content of the antiblocking agent is 5 to 10% by weight based on the weight of the ethylene-carboxylic acid copolymer.
10. The aqueous dispersion composition of claim 1 having a solids content of 20 to 50%.
Citation Information
Patent Citations
Improved spinning method
JP1986012913A
Protecting agent for coated surface
JP1989104671A
Aqueous resin composition
JP1992153239A
Water-disintegrable moistureproofing paper having light-shielding property and heat-sealability
JP1994184987A
Calorimeter for gas-flow adjusting type differential scanning
JP1996334484A